Immune Reconstitution Following Autologous Hematopoietic Stem Cell Transplantation for Multiple Sclerosis: A Review on Behalf of the EBMT Autoimmune Diseases Working Party - Cencioni, Maria Teresa; Genchi, Angela; Brittain, Gavin; de Silva, Thushan I.; Sharrack, Basil; Snowden, John Andrew; Alexander, Tobias; Greco, Raffaella; Muraro, Paolo A. (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is a central nervous system (CNS) disorder, which is mediated by an abnormal immune response coordinated by T and B cells resulting in areas of inflammation, demyelination, and axonal loss. Disease modifying treatments (DMTs) are available to dampen the inflammatory aggression but are ineffective in many patients. Autologous hematopoietic stem cell transplantation (HSCT) has been used as treatment in patients with highly active disease, achieving a long-term clinical remission in most. The rationale of the intervention is to eradicate inflammatory auto-reactive cells with lympho-ablative regimens and restore immune tolerance. Immunological studies have demonstrated that autologous HSCT induces a renewal of TCR repertoires, resurgence of immune regulatory cells and depletion of pro-inflammatory T cell subsets, suggesting a “resetting” of immunological memory. Although our understanding of the clinical and immunological effects of autologous HSCT has progressed, further work is required to characterise the mechanisms that underlie treatment efficacy. Considering that memory B cells are disease-promoting and stem-like T cells are multipotent progenitors involved in self-regeneration of central and effector memory cells, investigating the reconstitution of B cell compartment and stem and effector subsets of immunological memory following autologous HSCT could elucidate those mechanisms. Since all subjects need to be optimally protected from vaccine preventable diseases (including COVID-19), there is a need to ensure that vaccination in subjects undergoing HSCT is effective and safe. Additionally, the study of vaccination in HSCT-treated subjects as a mean of evaluating immune responses could further distinguish broad immunosuppression from immune resetting.